Modern marvels [ the weird and wonderful world of the everyday:corn and rats (Actuality Productions Inc, 2008)
Corn has fed the masses from ancient times to this day. Its unique properties make it ideal for a number of applications. From packing material to plasticizers to fuel, corn is not only a vegetable and cereal grain, it is a vital comodity. Visit Lakeside Foods in Reedsburg, Wisconsin and see how tons of corn are harvested and canned within hours. Then to VeraSun Energy in Charles City, Iowa, to discover how corn is